1987
DOI: 10.1111/j.1527-3466.1987.tb00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Tiapamil

Abstract: Tiapamil is a Ca2+ entry blocker that is under development for the treatment of mild to moderate hypertension and angina pectoris. It also possesses antiarrhythmic properties. This review focuses on the pharmacological, toxicological, and clinical properties of tiapamil. A comparison is made of the effects of tiapamil with the effects of some other Ca2+ entry blockers. CHEMISTRYTiapamil (Ro 1 1-178 1 , Larocord) is the hydrochloride monohydrate of N-(3,4-dimethoxyphenethy1)-2-(3,4-dimethoxyphenyl)-N-methyl-rn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Amyloid P component has been purified from the kidneys of a patient who had died of secondary amyloidosis. The molecular weight of the AP subiinil on 15"?^ SDS-PAGti gels was approximately 23.100, with an amino acid composition similar to those reported by Hoick et al [16] and Benson et al f6). Under the electron microscope.…”
Section: Discussionsupporting
confidence: 81%
“…Amyloid P component has been purified from the kidneys of a patient who had died of secondary amyloidosis. The molecular weight of the AP subiinil on 15"?^ SDS-PAGti gels was approximately 23.100, with an amino acid composition similar to those reported by Hoick et al [16] and Benson et al f6). Under the electron microscope.…”
Section: Discussionsupporting
confidence: 81%
“…[ 195 ] This drug caused a concentration‐dependent inhibition of [ 3 H]‐desmethoxy‐verapamil binding to pig cardiac membranes with an IC 50 of 250 nM. [ 196 ]…”
Section: Ion Channel Blockersmentioning
confidence: 99%
“…The antimhythmic properties of tiapamil appear to extend beyond the suppression of supraventricular tachycardia. Clinical trials have shown iv administered tiapamil to be effective in decreasing ventricular premature contractions and VT. [ 196 ] Despite successful clinical trials of the drug, it never entered the market.…”
Section: Ion Channel Blockersmentioning
confidence: 99%
See 1 more Smart Citation